2007
DOI: 10.1016/j.cancergencyto.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Allelic losses at genomic instability-associated loci in villous adenomas and adjacent colorectal cancers

Abstract: Allelic imbalances in premalignant villous adenomas were compared with those in adjacent microdissected colorectal carcinoma that had arisen directly from the adenomas. Carcinoma-adenoma pairs were examined from 17 patients who underwent resections for colorectal cancer. In all, 28 microsatellite markers were examined, from regions of the genome where individual allelic losses have been associated with overall genomic instability in colorectal carcinomas. Microsatellite instability (MSI) was also evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Genome-wide FAL rates do not significantly correlate with the smaller genomic events detected by ISSR-PCR and MSI, but loci on chromosomes 3,8,11,13,14,18, and 20 demonstrate significantly elevated instability by GII and/or FAL rate in LOHþ tumors [72]. A recent study from the same laboratory amplified 28 markers from microdissected tumors arising directly from villous adenomas and report a carcinoma mean FAL rate (0.135) significantly higher than that of the adjacent adenoma (0.052) [19]. The FAL rates reported for CRC and adenomas in this study were nearly twice that in their former study because the 28 markers chosen were already linked to LOH [19,72].…”
Section: Loss Of Heterozygositymentioning
confidence: 99%
See 2 more Smart Citations
“…Genome-wide FAL rates do not significantly correlate with the smaller genomic events detected by ISSR-PCR and MSI, but loci on chromosomes 3,8,11,13,14,18, and 20 demonstrate significantly elevated instability by GII and/or FAL rate in LOHþ tumors [72]. A recent study from the same laboratory amplified 28 markers from microdissected tumors arising directly from villous adenomas and report a carcinoma mean FAL rate (0.135) significantly higher than that of the adjacent adenoma (0.052) [19]. The FAL rates reported for CRC and adenomas in this study were nearly twice that in their former study because the 28 markers chosen were already linked to LOH [19,72].…”
Section: Loss Of Heterozygositymentioning
confidence: 99%
“…A recent study from the same laboratory amplified 28 markers from microdissected tumors arising directly from villous adenomas and report a carcinoma mean FAL rate (0.135) significantly higher than that of the adjacent adenoma (0.052) [19]. The FAL rates reported for CRC and adenomas in this study were nearly twice that in their former study because the 28 markers chosen were already linked to LOH [19,72]. These LOH markers in adenomas and CRC provide loci for further genetic profiling of ACF relative to tumor progression.…”
Section: Loss Of Heterozygositymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that individuals with adenomas and colorectal cancer (CRC) have a higher percentage of ACF as compared to patients without a similar pathology in the large intestine. It is important that in some studies ACF were found in the direct vicinity of adenomas as were adenomas found at the periphery of CRC [6,7]. An analysis of various studies shows that dysplastic ACF most commonly accompany adenomas and CRC [6].…”
Section: Introductionmentioning
confidence: 99%